Influence of Set Size on Yield and Quality in Off- Season Onion Production (Plant Bulletin, 2025)
Off-season onion production requires optimal set size to achieve a delicate balance of high yield and good quality. This study investigates the effect of different set sizes on onion production and quality. The experiments were conducted at Agricultural Research Institute Mingora, Swat, during 2021-2022. Five set sizes (9-12, 13-16, 17-20, 21-24, and 25-28 mm) were replicated three times in a randomized complete block design. Significant differences (P ≤ 0.01) were observed among the treatments for most of the studied traits, except plant height across the years. Bolting and splitting percentage increased with increased set size, while plant height, leaf number, bulb diameter, and single bulb weight increased with increased sets size. Sets with a diameter of 17-20 mm achieved maximum marketable bulb yield. Selecting the appropriate set size is crucial for balancing yield and quality in off-season onion production, as bolting, splitting, bulb diameter, and white rot traits have complex correlations with yield, increasing both productivity and disease risk.
Keywords: Onion autumn crop, Off-season